Dementia prevention, intervention, and care: 2024 report of the Lancet standing Commission - Livingston, Gill; Huntley, Jonathan; Liu, Kathy Y; Costafreda, Sergi G; Selbæk, Geir; Alladi, Suvarna; Ames, David; Banerjee, Sube; Burns, Alistair; Brayne, Carol; Fox, Nick C; Ferri, Cleusa P; et al. (The Lancet (British edition), 2024)
Evidence is increasing and is now stronger than before that tackling the many risk factors for dementia that we modelled previously (ie, less education, hearing loss, hypertension, smoking, obesity, depression, physical inactivity, diabetes, excessive alcohol consumption [ie, >21 UK units, equivalent to >12 US units], traumatic brain injury [TBI], air pollution, and social isolation) reduces the risk of developing dementia. Use of hearing aids appears to be particularly effective in people with hearing loss and additional risk factors for dementia. Key messages Two new modifiable risk factors for dementia New evidence supports adding vision loss and high cholesterol as potentially modifiable risk factors for dementia to the 12 risk factors identified in our 2020 Lancet Commission (ie, less education, head injury, physical inactivity, smoking, excessive alcohol consumption, hypertension, obesity, diabetes, hearing loss, depression, infrequent social contact, and air pollution). Make hearing aids accessible for people with hearing loss and decrease harmful noise exposure to reduce hearing loss